A case of partial anonychia with a review of literature - Jalde, Devendra D; Godhi, Satyajit A; Uppin, Shashi M (International Multidisciplinary Research Journal, 2012)
Anonychia (absence of the nails) from birth is a rare congenital anomaly. It may occur as an isolated sign, which is very rare or be accompanied by other defects of the digits and other structures. Of these abnormalities, the most frequent are some hypoplastic nails, absence of distal phalanges etc, this is incomplete anonychia. The mode of inheritance of most of these disorders has not yet been established with certainty. Very few cases of anonychia with the above mentioned disorders have been reported but this is probably the first report of a case of anonychia along with congenital absence of umbilicus.